2019
DOI: 10.1007/s11920-019-1072-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Brain Network Biomarkers of Antidepressant Response: a Review

Abstract: Purpose of Review Poor treatment response is a hallmark of major depressive disorder. To tackle this problem, recent neuroimaging studies have sought to characterize antidepressant response in terms of pretreatment differences in intrinsic functional brain networks. Our aim is to review recent studies that predict antidepressant response using intrinsic network connectivity. We discuss current methodological limitations and directions for future antidepressant biomarker studies. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 131 publications
(170 reference statements)
3
49
1
Order By: Relevance
“…There was a reduction in rsFC of the L. dACC after the course of ECT. Neuroimaging studies suggest increased activity in the ACC as an important biomarker for depression (Helm et al, 2018 ; Lai, 2019 ), which normalizes after treatment with antidepressants and serves as a predictor for the response (Arnone, 2019 ; Dunlop et al, 2019 ; Tian et al, 2020 ). However, sgACC/rACC are implicated here more often than dACC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a reduction in rsFC of the L. dACC after the course of ECT. Neuroimaging studies suggest increased activity in the ACC as an important biomarker for depression (Helm et al, 2018 ; Lai, 2019 ), which normalizes after treatment with antidepressants and serves as a predictor for the response (Arnone, 2019 ; Dunlop et al, 2019 ; Tian et al, 2020 ). However, sgACC/rACC are implicated here more often than dACC.…”
Section: Discussionmentioning
confidence: 99%
“…PCC is considered to be an important part of pDMN and is found to have increased FC with dmPFC in people having depression compared with controls (Mulders et al, 2015 ; Helm et al, 2018 ). Increased rsFC of PCC has been shown to be a predictor for response to antidepressants (Goldstein-Piekarski et al, 2018 ; Dunlop et al, 2019 ), psychotherapy (Dunlop et al, 2019 ), and ECT (van Waarde et al, 2015 ). Although there is evidence of reduction in FC of PCC with antidepressants in response to a negative emotional task in some studies, the evidence is limited in rsFC studies to overall increased activity in pDMN rather than in PCC specifically (Arnone, 2019 ; Ichikawa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain regions most consistently identified as abnormal prior to treatment, in either function or structure, included the amygdala, ventral striatum, thalamus, hippocampus, anterior cingulate cortex (ACC), ventromedial PFC (vmPFC), orbitofrontal cortex (OFC), and dorsolateral prefrontal cortex (dlPFC). More recent studies have emphasized the role of brain networks of which these structures are a part, rather than that of single structures [12]. Importantly, AD treatment effects have been mapped onto the widely accepted models of biological mechanisms of depression [13].…”
Section: Single Drug Studiesmentioning
confidence: 99%
“…PgACC plays a crucial role in the development of depressive symptoms and antidepressant response due to its central position between the circuits responsible for a quick automatic response to emotionally salient stimuli and prefrontal regions exerting cognitive control over them. A recent review [12] emphasized its role at the network level and suggested that functional connectivity from pgACC showed a particular consistency in predicting antidepressant response.…”
Section: Pregenual Anterior Cingulate Cortex (Pgacc): a General Respomentioning
confidence: 99%